2021
DOI: 10.1016/j.cose.2021.102387
|View full text |Cite
|
Sign up to set email alerts
|

Developing a cyber security culture: Current practices and future needs

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 56 publications
1
50
0
Order By: Relevance
“…Cybersecurity culture is a related concept that has recently emerged as relevant to consider. It has been described as a sub-culture of organisational culture, involving values and attitudes that drive cybersecurity behaviours within the organisation (Huang and Pearlson, 2019;Uchendu et al, 2021). In the literature, the terms of information security culture and cybersecurity culture are often used interchangeably, and a recent review of cybersecurity found few studies that considered any differences between the two (Uchendu et al, 2021).…”
Section: Value Conflicts and Information Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cybersecurity culture is a related concept that has recently emerged as relevant to consider. It has been described as a sub-culture of organisational culture, involving values and attitudes that drive cybersecurity behaviours within the organisation (Huang and Pearlson, 2019;Uchendu et al, 2021). In the literature, the terms of information security culture and cybersecurity culture are often used interchangeably, and a recent review of cybersecurity found few studies that considered any differences between the two (Uchendu et al, 2021).…”
Section: Value Conflicts and Information Securitymentioning
confidence: 99%
“…It has been described as a sub-culture of organisational culture, involving values and attitudes that drive cybersecurity behaviours within the organisation (Huang and Pearlson, 2019;Uchendu et al, 2021). In the literature, the terms of information security culture and cybersecurity culture are often used interchangeably, and a recent review of cybersecurity found few studies that considered any differences between the two (Uchendu et al, 2021). The same review explored factors important for creating and maintaining a cybersecurity culture and found that top management support and clear policies and procedures were important.…”
Section: Value Conflicts and Information Securitymentioning
confidence: 99%
“…There are two reasons why we decided to exclude papers published before 2010. First, we wanted to focus on more recent research (the past decade), which is a common practice for SLRs [89,182]. Our results showed that relevant research was indeed more done in the past several years (see Figure 2).…”
Section: Systematic Literature Review (Slr)mentioning
confidence: 95%
“…Cybersecurity culture is one aspect of organisational culture (Marotta and Pearlson, 2019), but a very important aspect especially in the context of this study. For example, Uchendu et al (2021) states that the Culture Domain has been heavily studied in the past decade in research and practice as organisations seek to combat increased cyberattacks that focus on exploiting human factors. It is important to recognise that organisations in certain verticals are known to be more regulated in certain respects than others, and hence may require more stringent compliance and enforcement cybersecurity culture.…”
Section: Figure 2: Cross-domain Situational Awarenessmentioning
confidence: 99%